The Influence of Halal Destination Awareness on Halal Destination Loyalty: A Study on West Sumatera - Anya Safira; Nabila Salsabilia (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2022)
Opportunities in developing Muslim-friendly tourist destinations in Indonesia are getting bigger along with the increasing Muslim population in Indonesia and in the world. Since receiving the spotlight as a country with several world-class Halal Tourism awards, Indonesia has begun to focus on developing Muslim-friendly tourism comprehensively. West Sumatra is one of the provinces that has become the focus of the Indonesian Ministry of Tourism and Creative Economy as a Muslim-friendly tourist destination in Indonesia with the aim to provide Muslim-friendly tourism services for the global Muslim community. This study was conducted to analyze the effect of Halal Destination Awareness on Halal Destination Loyalty of West Sumatra as a Muslim-friendly tourist destination. Data was collected using a self-administered questionnaire and 386 respondents were obtained and then processed using PLS Structural Equation Modeling with SmartPLS 3.0 software. This study found that halal brand destination awareness has an effect on halal destination brand loyalty in the selection of West Sumatra as a Muslim-friendly tourist destination. These results can be used as a reference for tourism industry players to maximize the potential and advantages possessed by West Sumatra as a Muslim-friendly tourism destination.